Multi-component screening coupled with ultrasound-assisted green extraction based on HPLC-HRMS for bio-actives analysis in saffron (Crocus sativus L.) - Shouying Wang; Yiqing Song; Miaomiao Chen; Bing Bai; Lin Zhou; Changyan Zhou; Yongchun Zhang; Zhiying Huang; Wenshuai Si (Food Chemistry: X)
A database of 115 bio-actives from seven subclasses, including information on retention time, parent ion m/z, fragment m/z, and isotopic fit, was established, and an instrumental method for simultaneous analysis of these targets was optimised. An ultrasound-assisted preparation method at 50 °C for 50 min with a 1:60 solid-liquid ratio, water as the solvent was proposed for the screening of unknown components and the antioxidant analysis in saffron. The self-built database and untargeted analysis identified 32 and 103 bio-actives in saffron, respectively. The comparative analysis revealed that the antioxidant capacity of saffron petals was superior to that of stigmas. Correlation and multivariate statistical analyses indicated that terpenoids may be the main active substances in stigmas, while flavonoids and carboxylic acid derivatives play a pivotal role in conferring antioxidant activity to de-stigmatised saffron. The method serves as an ideal tool for mining the functional components of saffron and other agricultural products.